The Critical Success Factors of Succession Planning In Malaysian Public Universities - Abd Rahman Ahmad, Nazia Keerio (International Journal of Advanced Science and Technology, 2020)
Succession planning is a crucial component for the development of future leaders and ensuring an institution meets its potential goals. This paper will briefly review the implementation of succession planning in Malaysian public universities. Finally, it will concentrate on factors influencing the succession planning cycle in Malaysian public universities. The main aim of this qualitative analysis is to identify the most important factors in the implementation of a succession planning program in Malaysian public universities. The individual interviews were conducted in selected public universities in Malaysia. Members of the designated sample have been selected from the directory on the institution’s website and have sent an initial invitation email contact describing the research study and inviting them to participate. All interviews have been recorded and transcribed for analysis. Using an interview schedule the primary data were obtained from the respondents. The interpretation of the data was achieved by thematic interpretation. The result indicates that public universities in Malaysia have implemented a succession planning system in their institutions. Here, participants have agreed that factors such as organizational culture, top management commitment, strategic plan, reward system, budget, IT system, and commitment from top management are among the critical success factors of the successful succession planning program in the Malaysian public universities. This research using a qualitative approach in order to identify the critical success factor of the succession planning in Malaysian public universities. Although the lack of consideration of these factors poses a challenge to the system, the outcome of this study may help other institutions consider implementing the succession planning program for better performance.